Characterization of a Small Supernumerary Marker Chromosome Derived from Xq28 and 14q11.2 Detected Prenatally - Akihiro Hasegawa; Osamu Samura; Taisuke Sato; Tomona Matsuoka; Yuki Ito; Kazuhiro Kajiwara; Hiroaki Aoki; Yuka Inage; Masahisa Kobayashi; Aikou Okamoto (Case Reports in Obstetrics and Gynecology)
We present the characterization of a case with a small supernumerary marker chromosome (sSMC) detected prenatally derived from Xq28 and 14q11.2 maternal translocation. A 33-year-old Japanese woman, primigravida, underwent amniocentesis because of fetal growth restriction and fetal structural abnormality at 30 weeks of gestation. The fetal karyotype was identified as 47,XY,+mar. Additionally, the single nucleotide polymorphism array analysis revealed copy number gains at Xq28 and 14q11.2. A male infant, weighing 1,391 g, was delivered at term by cesarean section. Maternal and paternal karyotypes were 46,X,t(X; 14)(q28; q11) and 46,XY, respectively. These findings indicated that the sSMC might have originated from chromosome disjunction at a ratio of three to one. Here we describe a case with an sSMC derived from Xq28 and 14q11.2. Our findings suggest that this sSMC is most likely pathogenic. The collection of additional cases may be required.